Relación entre la duración del vínculo marital heterosexual superior a 10 años con la satisfacción marital y los factores sociodemográficos (2024)
In the present research, the duration of the heterosexual marital bond of more than 10 years was related to marital satisfaction and sociodemographic factors of people resident in the city of Barranquilla who are in a marital union. This study was quantitative with an empirical-analytical, correlational, non-experimental and transactional design. The sample was accidental non-probabilistic, with 416 people responding to the calls made for the study. Regarding data collection, a sociodemographic survey was prepared and applied by the researchers, along with the Pick and Andrade’s Marital Satisfaction Scale (1988). The analysis of the results showed significant correlations between age and years of marital union, age and number of children, and the duration of the marital bond. Likewise, the crises that couples go through throughout their life cycle are significantly related to emotional and organizational aspects, and marital interaction with the spouse. This study showed that socioeconomic status and marital satisfaction are positively related. The organizational aspects of the spouse are positively related to marital satisfaction; and, finally, it is highlighted that people from a lower socioeconomic class tend to have a greater number of children than those from a higher socioeconomic level.